Development and characterization of gastro-floating sustained-release granules for enhanced bioavailability of patchouli oil - Chen Liu; Yanan Wu; Yeli Zou; Jiao Wang; Boli Li; Yanni Ma; Xia Zhang; Wenping Wang (Heliyon)
Patchouli oil (PO), extracted from Pogostemon cablin Benth., a prominent aromatic plant of the Lamiaceae family, has shown considerable protective effects against gastrointestinal infections, particularly those induced by Helicobacter pylori. This study aimed to develop a gastro-floating multi-unit system for PO to enhance its gastric retention and oral bioavailability. Methods: The oil-laden granules were prepared using colloidal silicon dioxide (CSD) for oil adsorption and to provide buoyancy, along with ethyl cellulose (EC) and hydroxypropyl methyl cellulose (HPMC) to form a sustained-release matrix. The CSD exhibited favorable characteristics for oil adsorption and floating. Compatibility between PO and CSD was affirmed through DSC thermograms and FTIR spectra. The obtained granules demonstrated a sustained release profile, achieving over 90 % release within 10 h without an initial burst. After oral administration, the granules were observed to remain in the gastric region of rats for over 7 h. The bioavailability of patchouli alcohol from the optimized granules was significantly higher than that from of the PO-loaded powders. The gastro-floating sustained-release granules, based on a CSD/EC/HPMC matrix, offer a simple yet effective strategy to improve the delivery efficacy of PO against Helicobacter pylori infections in the gastric region.